Student Reflective Practices - Rau, Herbert (Selected Topics in Humanities and Social Sciences Vol. 2, 2021)
For decades, reflective practices for professionals and students have been recommended by scholars. It is not clear, however, whether significant attention has been focused to understand if an inherent tendency towards the practice of reflection is demonstrated by students. A study was conducted to determine whether students demonstrate a propensity towards reflection, and if a tendency is identified, how that strategy is expressed. Further, utilizing the Human Dynamics model of Seagal and Horne, an attempt is made to determine whether particular dynamics exploit different reflective strategies.